Sustainable Tourism Management at Prambanan Temple: Analysis of Utilization, Cultural Preservation, and Local Community Welfare - Wingkie Nusanti; Amelda Pramezwari; Elang kusumo (International Journal Labs, 2025)
This study examines the implementation of sustainable tourism management at Prambanan Temple, focusing on the coordination challenges between PT Taman Wisata Candi (TWC) and the Cultural Heritage Preservation Center and Museum (BPK MCB), as well as the implications for economic equity, cultural preservation, and local community welfare. Using a qualitative case study approach, data were collected through in-depth interviews with pentahelix stakeholders (academics, industry players, communities, government, and media), direct observations, and documentation analysis. The findings reveal that although PT TWC has actively organized various cultural events and empowered local communities through MSME involvement and labor absorption, the economic benefits have not been evenly distributed, and community participation remains limited, particularly in the planning and evaluation stages. Coordination between PT TWC, which is oriented toward tourism utilization, and BPK MCB, which focuses on conservation, faces challenges due to differences in priorities, lack of structured formal meetings, and overlapping regulations at various administrative levels. Cultural preservation efforts are also at risk of over-commercialization that can erode authenticity and cultural values. This study concludes that effective sustainable tourism management requires regulatory synchronization, strengthening local community participation through a community-based tourism approach, fair distribution of economic benefits, and holistic collaboration among all stakeholders to balance tourism utilization, cultural heritage preservation, and local community welfare.